Patient safety culture and adverse event notification of a multidisciplinary health team (Research, Society and Development, 2021)
This study aimed to understand the patient safety culture and adverse event notification of a multiprofessional health team at a public teaching hospital. Cross-sectional study with data collection between December 2015 and March 2016, using the Hospital Survey on Patient Safety Culture questionnaire (HSOPSC). The sample was intentional, made up of all health professionals involved in health care. Of the participants (331), 44.0% were nursing technicians / auxiliaries, 28.4% were nurses, 17.1% were physicians and 10.5% were others. Considering the 42 questions of the instrument, a total of 5385 (39.7%) were positive, 3122 (23.0%) were neutral and 5066 (37.3%) were negative. It was observed that 78.3% of professionals reported no adverse events (AD) in the last 12 months and 52.8% considered the patient's safety score to be "regular". The most positive score was statistically related to professionals who had less than one year of work in the hospital (p=0.021), worked less than 80 hours a week (p=0.048), held a technical-level (p=0.010), full-time position (p=0.006), and those who had reported AE in the past 12 months (p=0.016). The safety culture of the patient in the study hospital is not yet structured, however highlighted positive aspects can be used as a starting point for implementing changes.